PERBEDAAN KECEMASAN ANAK USIA PRASEKOLAH PADA TINDAKAN INJEKSI DENGAN DITERAPKAN DAN TANPA DITERAPKAN PEMAKAIAN ROMPI BERGAMBAR DI RUANG MELATI RSUD ABDUL WAHAB SJAHRANIE SAMARINDA - Enok Sureskiarti; Marwah Maawiyah Nur Karina Brutu (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Children with painful procedures tend to exhibit negative behavioral reactions, such as children becoming more aggressive and uncooperative or hostile, and if these conditions continue to develop growth disturbances, it also complicates the implementation of medical procedures such as injecting drug. To know the difference of pre-school age anxiety at injection action by applied and without applying the wearing picture vest in Melati Room of RSUD Abdul Wahab Sjahranie Samarinda. This study used quasi experimentalposttest design only non equivalent control group. Anxiety was measured using the Children's Fear Scale measurement scale. The sample of the study was 30 children divided into groups of intervention and control. Analysis to see the effect between the two variables using Mann Whitney test. The frequency distribution of anxiety in the intervention group and the control group each had an average score of 0.64 (95% CI = 0.32-1.01) and 2.57 (95% CI = 1.50-3, 16). The result of this study was Mann Whitney's 0,003 (α = 0,05) analysis, indicating a difference between the intervention group and the control group. The results of mean difference analysis in the intervention and control group showed that there were differences in pre-school age anxiety at the injection action by applied and without applying the picture vest in the Melati Room of RSUD Abdul Wahab Sjahranie Samarinda. The use of pictured vests can be used as an effort to decrease children's anxiety at the injection action.